The fairies' shoemaker ... and other stories - Blyton, Enid (Bounty London, 2014)
''Marjorie is delighted to stumble across a mysterious little man and she discovers he's the fairies' shoemaker who makes beautiful shoes in every colour under the sun. Alongside stories of Pinkity the naughty pixie, Ding, Dong and Dell, and Twinks and Little-Toes, The Fairies' Shoemaker will provide endless fun and fascination. Other stories in this volume: The Careless Hedgehogs The Tree Naughty Gnomes The Naughty Smoke Fairies The Elephant and the Snail Sally Dumble's Trick Belinda and the Bulbs and many more ... '' -- Back cover